Brief Report: Aging Attenuates the Association Between Coronary Artery Calcification and Bone Loss Among HIV-Infected Persons. (1st September 2019) - Escota, Gerome; Baker, Jason; Bush, Tim; Conley, Lois; Brooks, John T.; Patel, Pragna; Powderly, William; Presti, Rachel; Overton, Edgar T.
Abstract : Introduction: Studies among HIV-uninfected persons (mostly in their sixth decade of life) show that detectable coronary artery calcium (CAC) is independently associated with low bone mineral density (BMD), suggesting a possible common pathogenic mechanism. Aim: We assessed the relationship between CAC and BMD, which has not been well described among younger to middle-aged HIV-infected persons. Methods: We studied participants with baseline CAC and BMD measures from a prospective cohort of HIV-infected persons enrolled in the Study to Understand the Natural History of HIV/AIDS in the Era of Effective Therapy (SUN) during 2004–2006. We used logistic regression to assess the association between detectable CAC (>0 Agatston score) and BMD (g/cm 2, T-score), and adjusted for known traditional and HIV-related risk factors. Results: Among 472 participants (76% male, 30% non-Hispanic black, median age 41 years, and 71% with HIV RNA < 400 copies/mL), the majority had no detectable CAC (82%), but had baseline osteopenia (53%) or osteoporosis (10%). In univariate analysis, participants with detectable CAC had lower femoral neck/total hip T-scores, lower femoral neck/total hip/lumbar spine BMD, and higher rates of osteopenia/osteoporosis. After adjustment for age, all associations were no longer significant; adjustment for traditional risk factors excluding age and HIV-related variables failed to attenuate these associations. Conclusions: We found aging attenuates the association between detectable CAC and BMD in this cohort. Aging remains an important contributor to non–AIDS-defining illnesses. These data reinforce the importance of developing screening and prevention strategies for aging HIV-infected persons given their excess risk across a wide spectrum of end-organ complications. Abstract : Supplemental Digital Content is Available in the Text.